2019
DOI: 10.3390/s19061298
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection of Cucumber Green Mottle Mosaic Virus Based on Terminal Deoxynucleotidyl Transferase Coupled with DNAzymes Amplification

Abstract: A simple, rapid, and sensitive visual detection method for observing cucumber green mottle mosaic virus was reported based on the template-independent polymerization activity of terminal deoxynucleotidyl transferase (TdT), coupled with the cascade amplification of Mg2+-dependent DNAzyme and hemin/G-quadruplex DNAzyme. Briefly, the hybridized dsDNA of T1/P1 was cut into two parts at its position of 5′-AA↓CG↑TT-3′ by the restricted enzyme AcII. The longer, newborn fragment originating from P1 was tailed at its 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
0
7
0
1
Order By: Relevance
“…Previous reports have employed a similar strategy to detect both human and plant viruses (Yang et al, 2017;Kim et al, 2018;Wang et al, 2019), and a recent report has suggested the potential use of DNAzyme sensors for SARS-CoV-2 detection (Xi et al, 2020). We here demonstrate the utility of this approach for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 58%
“…Previous reports have employed a similar strategy to detect both human and plant viruses (Yang et al, 2017;Kim et al, 2018;Wang et al, 2019), and a recent report has suggested the potential use of DNAzyme sensors for SARS-CoV-2 detection (Xi et al, 2020). We here demonstrate the utility of this approach for SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 58%
“…图 17 基于OTA适配体和TDT介导超长聚胸腺嘧啶转换的 Cu NPs的OTA荧光测定示意图 [49] (网络版彩图) 图 19 基于近端双向酶修复扩增的ATP荧光检测原理图 [51] (网络版彩图) 图 18 末端脱氧核苷酸转移酶(TdT)辅助扩增策略在黄瓜 绿斑驳花叶病毒视觉检测中的应用原理图 [50] (网络版彩图) [46] (网 络版彩图) 图 21 基于NIEP的E-DNA生物传感原理 [52] (网络版彩图)…”
Section: 酶解交联水凝胶unclassified
“…Figure18 Schematic diagram of the application of terminal deoxynucleotidyl transferase (TdT) assisted amplification strategy in the visual detection of cucumber green mottle mosaic virus[50] (color online).…”
mentioning
confidence: 99%
“…31 They are used in a variety of label-free biosensors due to the advantages of simple use, cost-effectiveness, easy modication and acquisition. 32,33 G-quadruplex-related strategies are also coupled with signal amplication steps, for example strand displacement amplication 34,35 and RCA 36 to elevate the sensitivity. RCA produces large weight ssDNA with G-rich sequences using circular ssDNA as template bearing trans-complementary G-quadruplex sequences.…”
mentioning
confidence: 99%